Abordaje psicológico desde el enfoque cognitivo conductual para la adherencia al tratamiento de Diabetes Mellitus tipo 1 y 2 en adolescentes: una revisión sistemática (2019)
Objective: To identify psychological interventions from a cognitive behavioral approach associated with treatment adherence in adolescents diagnosed with DM1 and DM2, by means of a systematic literature review. Methodology: A search was conducted (since 2014), in the databases: Elsevier, PubMed, NCBI, PsycINFO, Scielo and Redalyc, using English terms related to diabetes, adolescent, nonadherence, psychological intervention. Inclusion criteria; adolescents, diabetes mellitus type 1 and 2, psychological factors, treatment adherence, cognitive behavioral, psychological intervention, 2014-2019, English and Spanish literature, Portuguese, primary caregivers. Results: 7,400 studies were identified among all databases, 7,033 were excluded by title, 97 were reviewed by title and abstract, of which 50 were eliminated, based on title and abstract 44 were selected for full review of which only 7 met the inclusion criteria. The participants were between 10 and 18 years of age. The most commonly used study designs were randomized controlled trials. Interventions are given from positive psychology, dialectical behavioral therapy, and cognitive behavioral therapy. Discussion: It has been shown that the complications of DM can produce a significant decrease in quality of life, especially due to the physical limitations that can be caused by inadequate adherence to treatment. The most frequent psychological interventions are motivational interviewing and problem solving.